Brief Research Report: Serum clara cell 16 kDa protein levels are increased in patients hospitalized for severe SARS-CoV-2 or sepsis infection - Rohmann, Nathalie; Stürmer, Paula; Geisler, Corinna; Schlicht, Kristina; Hartmann, Katharina; Türk, Kathrin; Hollstein, Tim; Tran, Florian; Rosenstiel, Philip; Franke, Andre; Heyckendorf, Jan; Schreiber, Stefan; et al. (Frontiers in Immunology, 2022)
Background: Clara cell 16 kDa protein (CC16) is a secretory protein primarily expressed in epithelial cells in the lungs. Previous studies show that CC16 exerts anti-inflammatory and immune-modulatory properties in both acute and chronic pulmonary diseases. However, despite the evidence of CC16’s high biomarker potential, evaluation of its role in infectious diseases is yet very limited. Methods: Serum CC16 concentrations were measured by ELISA and assessed in two different types of severe infections. Using a case-control study design, patients treated for either severe SARS-CoV-2 or severe non-pulmonary sepsis infection were compared to age- and sex-matched healthy human subjects. Results: Serum CC16 was significantly increased in both types of infection (SARS-CoV-2: 96.22 ± 129.01 ng/ml vs. healthy controls: 14.05 ± 7.48 ng/ml, p = 0.022; sepsis: 35.37 ± 28.10 ng/ml vs. healthy controls: 15.25 ± 7.51 ng/ml, p = 0.032) but there were no distinct differences between infections with and without pulmonary focus (p = 0.089). Furthermore, CC16 serum levels were positively correlated to disease duration and inversely to the platelet count in severe SARS-CoV-2 infection. Conclusions: Increased CC16 serum levels in both SARS-CoV-2 and sepsis reinforce the high potential as a biomarker for epithelial cell damage and bronchoalveolar‑blood barrier leakage in pulmonary as well as non-pulmonary infectious diseases.